ASSESSMENT OF MAGNESIUM OXIDE (MGO) AND SILICA DIOXIDE (SIO2) NANO-FLUIDS ADDITION WITH SURFACTANTS AS NEW TECHNIQUE TO CONTROL FINES MIGRATION - Lim Wan Ern; Asif Zamir; Sonny Irawan (Platform, a Journal of Engineering, 2020)
Formation damage in oil reservoirs because of fines migration is among the main contributors to productivity decline. Conventionally, chemical methods such as complex organic polymers are used to prevent fines migration by stabilizing or maintain the fines particles in aggregated form. However, most of the chemical fines stabilizer is not robust, which functionalize based on the composition of exchangeable cations in clay minerals, temporary stabilization and are not environmentally friendly. In this research work, qualitative methods were developed to investigate the potential of Magnesium Oxide (MgO) and Silica Dioxide (SiO2) Nano-Fluids addition with surfactants (Triton X-100 and Tween 80) as a new technique to control fines migration. Silicon Dioxide nanoparticles used in this experiment are in the form of colloidal silica with spherically sized at 10-15 nm then stabilized electrostatically to allow the particles to stay suspended in the solution. To measure the Nano-Fluids and fines solution stability, the minerals (kaolinite, bentonite and illite-smectite) crushed and suspended in 100 mL distilled water with 0.20%, 0.50%, 1.50% and 3% concentration, respectively. The suspended fines solutions left for 24 hours. Solution stability measured using the Zetasizer Nano ZSP by recording their turbidity (NTU) and zeta potential (mV). The results from the assessment shown that bentonite and kaolinite fines are more susceptible to migration in sandstone reservoirs due to their high colloidal stability from their zeta potential measurements and their morphologies. It can also be concluded that Silicon Dioxide (SiO2) is more stable when these nanoparticles are suspended in de-ionized water only, which gives zeta potential values of -26.10 mV. The addition of surfactants (Triton X-100 and Tween 80) has also shown significant results on protected fines migration. Triton X-100 and Tween 80 increased Silicon Dioxide (SiO2) Nano-fluid zeta potential value at -30.6 mV, which is beneficial for the Nano-Fluid to travel deeper into the formation to treat problematic areas of fines migration.